If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying half(7x + -2) + 5 = 2x + 7 Reorder the terms: afhl(-2 + 7x) + 5 = 2x + 7 (-2 * afhl + 7x * afhl) + 5 = 2x + 7 (-2afhl + 7afhlx) + 5 = 2x + 7 Reorder the terms: 5 + -2afhl + 7afhlx = 2x + 7 Reorder the terms: 5 + -2afhl + 7afhlx = 7 + 2x Solving 5 + -2afhl + 7afhlx = 7 + 2x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -2afhl + -5 + 7afhlx = 7 + -5 + 2x Reorder the terms: 5 + -5 + -2afhl + 7afhlx = 7 + -5 + 2x Combine like terms: 5 + -5 = 0 0 + -2afhl + 7afhlx = 7 + -5 + 2x -2afhl + 7afhlx = 7 + -5 + 2x Combine like terms: 7 + -5 = 2 -2afhl + 7afhlx = 2 + 2x Reorder the terms: -2 + -2afhl + 7afhlx + -2x = 2 + 2x + -2 + -2x Reorder the terms: -2 + -2afhl + 7afhlx + -2x = 2 + -2 + 2x + -2x Combine like terms: 2 + -2 = 0 -2 + -2afhl + 7afhlx + -2x = 0 + 2x + -2x -2 + -2afhl + 7afhlx + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 -2 + -2afhl + 7afhlx + -2x = 0 The solution to this equation could not be determined.
| 3a^2-8a+4=0 | | 3x+8=2x+1 | | 8x-5=8(x+6) | | -7n-3(n+7)=3-6n | | -72-3(n+7)=3-6n | | 7+(-3)v=6+v | | y=hx+f | | 3x^3+14x^2-12x=0 | | 9c+5-6=9 | | 5x^3-3x-2=0 | | 16x=12x+52 | | X-1=2y | | a^3b^5x=a^7b^5c^3 | | 3y^5*6y= | | 12x(x+1)=42(x+1)-(3x-42) | | 4.5=-3(-2.5)+b | | 2n-14=-8(7+5n) | | 2n-1=-8(7+5n) | | 3.14r^2=5 | | 3(3.5x+3.75)=3(4.75x+4) | | 6x-2=3x-44 | | 9e-5=22 | | 6x-1=2x-93 | | 25X^2+8X=0 | | 60=5x-5 | | 7(4x-9)+10=5x-5 | | 9x-4=75 | | -15x=1479 | | 9-7x=209-42x | | 3x+30=3 | | -3x+6x^2+5x+9x= | | 300-3P=3P |